Governance fit for climate change in a Caribbean coastal-marine context. (January 2015) - Pittman, Jeremy; Armitage, Derek; Alexander, Steven; Campbell, Donovan; Alleyne, Marium
Abstract: Coastal-marine systems in small island developing states of the Caribbean are highly vulnerable to both current and future climate change. Societies navigate these changes in part through processes of governance and the institutions through which governance takes place. The concept of institutional adaptive capacity is used to explore how governance processes and institutional arrangements can be adapted to match the scale and extent of climate change in a case study of the Soufriere Marine Management Area, St. Lucia. Institutional adaptive capacity is analyzed based on the following factors: institutional variety, analytical deliberation and nesting and networks. The analysis is based on 36 semi-structured interviews conducted with key informants from NGOs, cooperatives, management authorities and government agencies. The findings suggest that governance to address climate change in the case study is contingent upon developing holistic, integrated management systems, improving flexibility in existing collaborative decision making processes, augmenting the capacity of local management authorities with support from higher-level government, exploring opportunities for private–social partnerships, and developing adequate social–environmental monitoring programs. These findings have potential implications and lessons for similar settings throughout the Caribbean.